Freedom of information under official secrets act: a comparative study between Malaysia and United Kingdom / Husna Ridzuan...[et al.] - Ridzuan, Husna; Azman, Nur Ain; Azman, Nurina Khaliesya; Mahat, Nurul Farahhin (Faculty of Law, 2008)
In 1st October 1972, Official Secret Act has officially enacted which purposely to preserve certain document which is officially secret to the government. After the codification, the first amendment to the act has been made during 1984 followed by 1986. The legislation of the Official Secret Act in Malaysia is said to deprived the people's right to excess certain information has been restrained and consequently raised the dissatisfaction among the people.' Prior to this issue, researchers decided to conduct the study on the application of the freedom of infonnation in the context of Official Secret Act. Research revolved on the comparison between the Official Secret Act legislation in Malaysia and United Kingdom since the legislation in Malaysia is derived from and being in pari materia with the legislation of the United Kingdom. Different sources have been obtained in achieving the purpose of this study. The research was done by reference to the legislations that are the Malaysia's Official Secret Act 1972, as well as the Official Secret Act in United Kingdom. Besides, despite of the digital sources from the internet, the reference to the case study, books and journals is also used in order to gain more information regarding the decided topic. Towards the end of the study, researchers come up with the suggestion on how to overcome the weakness and to enhance the effectiveness of the Malaysian legislation